On (p^a,p^b,p^a,p^{a-b})-relative difference sets - Schmidt, Bernhard (2009)
This paper provides new exponent and rank conditions for the existence of abelian relative (p^a,p^b,p^a,p^a-b) -difference sets. It is also shown that no splitting relative (2^2c,2^d,2^2c,2^2c-d)-difference set exists if d > c and the forbidden subgroup is abelian. Furthermore, abelian relative (16, 4, 16, 4)-difference sets are studied in detail; in particular, it is shown that a relative (16, 4, 16, 4)-difference set in an abelian group G\not\cong Z_8× Z_4× Z_2 exists if and only if \exp(G)\le 4 or G= Z_8× ( Z_2)^3 with N\cong Z_2× Z_2.